The change in the frequency and severity of facial dermatoses and complaints in healthcare workers during the COVID‐19. (2nd June 2022) - Cosansu, Nur Cihan; Yuksekal, Gulcan; Kutlu, Omer; Umaroglu, Mutlu; Yaldız, Mahizer; Dikicier, Bahar Sevimli
Abstract: Background: The coronavirus disease 2019 (COVID‐19) pandemic has led to a dramatic increase in the use of personal protective equipment (PPE). However, the increased use of PPEs may lead to facial skin complaints. Aims: This survey study aims to evaluate the effect of the COVID‐19 pandemic on facial dermatoses and complaints. Methods: A total of 1017 volunteers (age 18–60 years), consisting of healthcare workers, participated in the study. In the present study, healthcare professionals were screened for facial dermatoses and complaints between 1 and 15 April 2021 with an online survey. Results: The vast majority of the survey were women (82.4%) and between 26 and 35 years old (49.2%). The most new‐onset facial complaints were acne (25.3%) and lip dryness (29.2%). Along with the pandemic, 50.9% of patients with seborrheic dermatitis had an increase in lesions. Another remarkable result was a 60.5% increase in acne complaints. Moreover, the rate of exacerbations of rosacea, melasma, and lip dryness was increased after the COVID‐19 pandemic (39.1%, 22.0%, and 42.7%, respectively). Exacerbations of seborrheic dermatitis, acne, and lip dryness have occurred more frequently in females when compared to males ( p  < 0.001). Conclusions: The current pandemic has had serious impacts on facial dermatoses which had to be managed carefully. Compared to the pre‐pandemic period, there was a significant increase in the frequency and severity of complaints in facial dermatoses related to PPE. If the complaints that may develop due to PPE are known in advance, their development can be prevented by taking precautions against them.